2023
DOI: 10.3389/fphar.2022.1078090
|View full text |Cite|
|
Sign up to set email alerts
|

Anticancer applications of phytochemicals in gastric cancer: Effects and molecular mechanism

Abstract: Gastric cancer (GC) is the fourth most common malignant cancer and is a life-threatening disease worldwide. Phytochemicals have been shown to be a rational, safe, non-toxic, and very promising approach to the prevention and treatment of cancer. It has been found that phytochemicals have protective effects against GC through inhibiting cell proliferation, inducing apoptosis and autophagy, suppressing cell invasion and migration, anti-angiogenesis, inhibit Helicobacter pylori infection, regulating the microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 157 publications
0
5
0
Order By: Relevance
“…Accumulated evidence and epidemiological investigations have reflected that natural product, including phytochemicals, have been explored potentially for the prevention and treatment of cancers and found to be useful in developing drugs and medicines counteracting and managing cancers, including gastric cancer caused by H. pylori infection [ [17] , [19] , [20] , [83] ]. Notably, various studies have suggested that mentioned bioactive phytochemical components with structural stability, potential bioavailability, and bioactivity could play a crucial role in formulating novel treatment regimens for gastric cancer management while minimizing the adverse effects associated with chemotherapeutic drugs as well as being comparatively safer.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence and epidemiological investigations have reflected that natural product, including phytochemicals, have been explored potentially for the prevention and treatment of cancers and found to be useful in developing drugs and medicines counteracting and managing cancers, including gastric cancer caused by H. pylori infection [ [17] , [19] , [20] , [83] ]. Notably, various studies have suggested that mentioned bioactive phytochemical components with structural stability, potential bioavailability, and bioactivity could play a crucial role in formulating novel treatment regimens for gastric cancer management while minimizing the adverse effects associated with chemotherapeutic drugs as well as being comparatively safer.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides, especially those derived from fungi, algae, tea, APS, Dendrobium, and other edible plants and herbs, are recognized for their anticancer properties against GC [62]. The anti-GC effects of APS are manifested not only in the enhancement of immune activity and the direct inhibition of tumor cell proliferation but also in the alleviation of adverse reactions to anticancer drugs [57,68,170,[185][186][187][188][189].…”
Section: Malignant Tumors Of the Digestive Systemmentioning
confidence: 99%
“…A notable statistic underscores the significance of natural origins, indicating that 51% of the 1211 newly approved small-molecule drugs worldwide between 1981 and 2014 were derived from natural products [ 20 ]. Polyphenols have been known to have various preventive effects on different conditions such as diabetes, cardiovascular disease, neurodegenerative disorder, and obesity [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and have been extensively studied to determine their anticancer potential and incorporate them into cancer treatment modalities like chemotherapy and targeted therapy [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%